KAPASITAS LENTUR PLAT BETON BERTULANGAN BAMBU PETUNG DENGAN TAKIKAN SEJAJAR - Cholid, Abdurrahman; Setiya Budi, Agus; Prayitno, Slamet (Program Studi Teknik Sipil FT UNS, 2014)
The main need for the use of reinforced concrete reinforcing steel as a major component in the construction of housing is increasing. Increasedneed for steel reinforcement will lead to increase of the price that it becomes expensive and scarce. To overcome these problems,it is necessary seek a alternative replacement of steel reinforcement in concrete. The results of the investigation reported in reference,stating that bamboo petung can be used as an alternative to replacement of concrete reinforcing steel because it has a high tensilestrength approaching the strength of steel. Bamboo reinforcement model approach is done by making notches on the sides parallel. Thisis expected to increase the strong adhesion between bamboo and concrete as the use of steel deformed bar. This research uses experimentalmethods to test object used is concrete slab measuring 600x400x100 mm. Quality concrete is planned fc '=15MPa. Bendingtest performed at 28 days with the third point loading method. In the analysis, the bending capacity of the slab with the notch parallelbamboo petung reinforcement is larger, is 0,2584 ton.m when compared with the results of the test slab which is an average of0,2356 ton.m. The pattern collapse on bamboo reinforced concrete slab is located between the parallel notches third middle span. Sucha collapse is included in the bending collapse. Collapse that occurs in the concrete slab by using bamboo as reinforcement petung bebrittle.